Predictive testing of minors for Huntington's disease: The UK and Netherlands experiences. Issue 1 (2nd November 2017) - Quarrell, Oliver W.; Clarke, Angus J.; Compton, Cecilia; de Die‐Smulders, Christine E.M.; Fryer, Alan; Jenkins, Sian; Lahiri, Nayana; MacLeod, Rhona; Miedzybrodzka, Zosia; Morrison, Patrick J.; Musgrave, Hannah; O'Driscoll, Mary; et al.
Abstract : A consistent feature of predictive testing guidelines for Huntington's disease (HD) is the recommendation not to undertake predictive tests on those < 18 years. Exceptions are made but the extent of, and reasons for, deviation from the guidelines are unknown. The UK Huntington's Prediction Consortium has collected data annually on predictive tests undertaken from the 23 UK genetic centers. DNA analysis for HD in the Netherlands is centralized in the Laboratory for Diagnostic Genome Analysis in Leiden. In the UK, 60 tests were performed on minors between 1994 and 2015 representing 0.63% of the total number of tests performed. In the Netherlands, 23 tests were performed on minors between 1997 and 2016. The majority of the tests were performed on those aged 16 and 17 years for both countries (23% and 57% for the UK, and 26% and 57% for the Netherlands). Data on the reasons for testing were identified for 36 UK and 22 Netherlands cases and included: close to the age of 18 years, pregnancy, currently in local authority care and likely to have less support available after 18 years, person never having the capacity to consent and other miscellaneous reasons. This study documents the extent of HD testing of minors in the UK and the Netherlands and suggests that, in general, the recommendation is being followed. We provide some empirical evidence as to reasons why clinicians have departed from the recommendation. We do not advise changing the recommendation but suggest that testing of minors continues to be monitored.